An analysis of the medical indications for preterm birth in an obstetrics and gynaecology teaching hospital in Shanghai, China. (April 2016) - Xue, Qinqin; Shen, Fang; Gao, Yanyun; Tong, Mancy; Zhao, Min; Chen, Qi
Abstract: Objective: preterm birth is a major cause of perinatal mortality and common cause of death in children under five years old. Although the indications for preterm birth are not fully understood, the preterm birth rate is around 11% worldwide dependent on the regions. China was cited as having a high death rate of children under five years old and one of the leading causes is preterm birth. This study sought to provide some information about preterm birth in China. Design: retrospective survey of maternal medical records. Setting: large Obstetrics and Gynaecology university teaching hospital in Shanghai, China. Participants: all women with live births from 2010 to 2012. Methods: descriptive analysis with χ 2 test. Main outcome measurements: whether birth was preterm (<37 weeks gestation), reasons for preterm birth. Findings: there were 37, 443 live births and 2541 preterm births (6.8%, 95%CI 6.5% to 7.0%) in the study period. The preterm birth rate in China is low compared with the worldwide rate. Most preterm births (85.2%) occurred at 33–37 weeks of gestation, with only 0.6% occurring before 28 weeks. Medical indications (49.3%) contributed most to preterm birth, followed by premature rupture of the membranes (39.5%) and spontaneous preterm birth (11.2%). The leading primary medical indications of preterm birth were preeclampsia, fetal distress, multiple pregnancies and placental complications. Conclusion: our data suggests preterm birth in China is low and medical indications are responsible for the majority of preterm birth. Highlights: The preterm birth rate in Chinese women was 6.8% compared to a worldwide rate of 11%. 85.2% of preterm birth occurred at 33–37 weeks of gestation with 0.6% before 28 weeks. 8.6% of women with preterm births were aged over 35 whereas only two were aged under 18.